Clonality, virulence and antimicrobial resistance of enteroaggregativeEscherichia colifrom Mirzapur, Bangladesh. Issue 10 (October 2017) - Chattaway, Marie Anne; Day, Michaela; Mtwale, Julia; White, Emma; Rogers, James; Day, Martin; Powell, David; Ahmad, Marwa; Harris, Ross; Talukder, Kaisar Ali; Wain, John; Jenkins, Claire; et al.
Abstract : Purpose. : This study investigates the virulence and antimicrobial resistance in association with common clonal complexes (CCs) of enteroaggregative Escherichia coli (EAEC) isolated from Bangladesh. The aim was to determine whether specific CCs were more likely to be associated with putative virulence genes and/or antimicrobial resistance. Methodology. : The presence of 15 virulence genes (by PCR) and susceptibility to 18 antibiotics were determined for 151 EAEC isolated from cases and controls during an intestinal infectious disease study carried out between 2007‐2011 in the rural setting of Mirzapur, Bangladesh (Kotloff KL, Blackwelder WC, Nasrin D, Nataro JP, Farag TH et al. Clin Infect Dis 2012;55:S232‐S245). These data were then analysed in the context of previously determined serotypes and clonal complexes defined by multi‐locus sequence typing. Results. : Overall there was no association between the presence of virulence or antimicrobial resistance genes in isolates of EAEC from cases versus controls. However, when stratified by clonal complex (CC) one CC associated with cases harboured more virulence factors (CC40) and one CC harboured more resistance genes (CC38) than the average. There was no direct link between the virulence gene content and antibiotic resistance. Strains within a single CC had variable virulence and resistance gene content indicating independent and multiple gene acquisitions over time. Conclusion. : In Bangladesh, there are multiple clonal complexes of EAEC harbouring a variety of virulence and resistance genes. The emergence of two of the most successful clones appeared to be linked to either increased virulence (CC40) or antimicrobial resistance (CC38), but increased resistance and virulence were not found in the same clonal complexes.